Electrooxidation in Alkaline Media of Ethylene Glycol and Glycerol on Pd‐(Ni‐Zn)/C Anodes in Direct Alcohol Fuel Cells. Issue 3 (4th March 2013) - Marchionni, Andrea; Bevilacqua, Manuela; Bianchini, Claudio; Chen, Yan‐Xin; Filippi, Jonathan; Fornasiero, Paolo; Lavacchi, Alessandro; Miller, Hamish; Wang, Lianqin; Vizza, Francesco
Abstract Invited for this month's cover is the group of Francesco Vizza at ICCOM‐CNR in Florence. The image shows a direct alcohol fuel cell that acts as a chemical reactor for the sustainable production of energy and chemicals. Read the full text of the article at http://dx.doi.org/10.1002/cssc.201200866.